Hypothermia impairs glymphatic drainage in traumatic brain injury as assessed by dynamic contrast-enhanced MRI with intrathecal contrast - Gu, Wenquan; Bai, Yingnan; Cai, Jianguo; Mi, Honglan; Bao, Yinghui; Zhao, Xinxin; Lu, Chen; Zhang, Fengchen; Li, Yue-hua; Lu, Qing (Frontiers in Neuroscience, 2023)
Introduction The impact of hypothermia on the impaired drainage function of the glymphatic system in traumatic brain injury (TBI) is not understood. Methods Male Sprague–Dawley rats undergoing controlled cortical impact injury (CCI) were subjected to hypothermia or normothermia treatment. The rats undergoing sham surgery without CCI were used as the control. Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) with intrathecal administration of low- and high-molecular-weight contrast agents (Gd-DTPA and hyaluronic acid conjugated Gd-DTPA) was performed after TBI and head temperature management. The semiquantitative kinetic parameters characterizing the contrast infusion and cleanout in the brain, including influx rate, efflux rate, and clearance duration, were calculated from the average time-intensity curves. Results and discussion The qualitative and semiquantitative results of DCE-MRI obtained from all examined perivascular spaces and most brain tissue regions showed a significantly increased influx rate and efflux rate and decreased clearance duration among all TBI animals, demonstrating a significant impairment of glymphatic drainage function. This glymphatic drainage dysfunction was exacerbated when additional hypothermia was applied. The early glymphatic drainage reduction induced by TBI and aggravated by hypothermia was linearly related to the late increased deposition of p-tau and beta-amyloid revealed by histopathologic and biochemical analysis and cognitive impairment assessed by the Barnes maze and novel object recognition test. The glymphatic system dysfunction induced by hypothermia may be an indirect alternative pathophysiological factor indicating injury to the brain after TBI. Longitudinal studies and targeted glymphatic dysfunction management are recommended to explore the potential effect of hypothermia in TBI.